Cryogelation reactions and cryogels: principles and challenges - Okay, Oğuz (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2023)
Cryogelation is a powerful technique for producing macroporous hydrogels called cryogels. Although cryogelation reactions and cryogels were discovered more than 70 years ago, they attracted significant interest only in the last 20 years mainly due to their extraordinary properties compared to the classical hydrogels such as a high toughness, almost complete squeezability, a mechanically stable porous structure with honeycomb arrangement, poroelasticity, and fast responsivity against external stimuli. In this mini review, general properties of cryogelation systems including the cryoconcentration phenomenon responsible for the unique properties of the cryogels are discussed. The squeezability and poroelasticity of cryogels comparable to those seen with articular cartilage are also discussed. Cryogelation reactions conducted within the pores of preformed cryogels and some novel cryogels with attractive properties are then discussed in the last section.
Keywords: Research Article